Experiments with a zigbee wireless communication system for self-reconfiguring modular robots - Fitch, R.; Lal, R. (2009 IEEE International Conference on Robotics and Automation, 2009)
The problem of designing reliable low-cost communications systems to support decentralized algorithms is a major research challenge in self-reconfiguring modular robotics. In this paper we evaluate a communication system based on ZigBee, a wireless ad-hoc mesh networking standard. We present a 15-node system prototype and results from an experiment of 300 trials that measures system performance on a benchmark task. The benchmark we chose is the connectivity problem - how to maintain connectivity in the module graph during the disconnections and reconnections that occur during reconfiguration. We also provide full implementation details in pseudocode for our connectivity algorithm. Our results show that, despite its inherent scalability limitations, a ZigBee wireless system is feasible as a simple, low-cost communication system for self-reconfiguring modular robots.